Answer:
See Below
Explanation:
The equation of f(x) isn't given so I will assume one equation for f(x) and solve the problem to show the process. The answer choices won't hold.
New Problem:
Find (g ∘ f)(10) when f(x) = 3x - 1 and g(x) = 2x + 3
Solution:
The notation (g ∘ f)(10) means take the function "f" and put it into "g" and then evaluate that expression with "10". First, lets find (g ∘ f)(x).
f(x) = 3x - 1
g(x) = 2x + 3
(g ∘ f)(x) = 2(3x - 1) + 3
= 6x - 2 + 3
= 6x + 1
So,
(g ∘ f)(x) = 6x + 1
Now,
(g ∘ f)(10) = 6(10) + 1 = 61
This would be the answer.